Implementasi dan Analisis Performa Protokol Message Queuing Telemetry Protocol Jaringan Smart Farming Pada Budidaya Jamur Tiram Dengan Memanfaatkan Internet Of Things - Pambudi, Sidiq Rilo; Subardono, Alif (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2021)
Abstract – The development of technology, gives many effects for human life. Many things can be controlled automatically and remotely. Internet of Things is as one of technology development which can be a solution to make human life easier. Internet of Things can also be used in agriculture sector and smart farming. Oyster growth is very affected by temperature and humidity. The temperature needed for growing of oyster is 24-28 Celsius degree. The use of Internet of Things is needed to monitor, take care and increase the productivity. Implementation of Smart Farming in agriculture sector, such as the using of protocol Message Queuing Telemetry Transport (MQTT) as a media of data traffic among censor, server and receiver of data. Message Queuing Telemetry Transport (MQTT) as protocol which can work as real time and work in low bandwidth, so the traffic of data works smoothly although in low bandwidth Keywords: Internet Of Things , Smart Farming, MQTT, QoS Intisari – Perkembangan teknologi memberikan banyak dampak pada kehidupan manusia. Banyak hal dapat dikontrol otomatis dari jarak jauh. Internet of Things (IoT) sebagai teknologi yang dapat menjadi solusi untuk mempermudah pekerjaan manusia. Internet of Things (IoT) dapat digunakan pula di bidang pertanian atau perkebunan pintar (Smart Farming). Tanaman Jamur Tiram sangat dipengaruhi oleh temperatur dan kelembaban. Kondisi udara saat pertumbuhan Jamur Tiram berada pada suhu 24-28 derajat Celcius. Penggunaan Internet of Thing (IoT) di bidang pertanian dapat mendukung pemantauan, perawatan dan meningkatkan produktifitas. Penerapan Smart Farming di bidang pertanian salah satunya dengan menggunakan protocol Message Queuing Telemetry Transport (MQTT) sebagai sarana lalu lintas data antara sensor, server dan penerima data. Message Queuing Telemetry Transport (MQTT) merupakan protocol yang dapat bekerja secara realtime dan dapat bekerja pada bandwidth yang rendah, sehingga lalu lintas data tetap lancar walaupun menggunakan bandwidth yang rendah. Kata Kunci : Internet Of Things , Smart Farming, MQTT, QoS